The role and regulation of PEPcarboxylase in dissolved inorganic carbon metabolism under Pi starvation in legume root systems - Ward, Caroline (Caroline Linda) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2004.